Early prediction of individual outcome following cardiopulmonary resuscitation: systematic review. Issue 10 (27th September 2005) - Kaye, P
Abstract : Following resuscitation from cardiorespiratory arrest 80% of patients are comatose. Of these patients, 20% will survive and regain consciousness. Is it possible to predict an individual's long term outcome at presentation and alter management accordingly? This review examines the current medical literature and demonstrates it is impossible to predict immediately outcome from hypoxic-ischaemic coma except in a small subgroup of patients with poor premorbid factors. As individual prognosis cannot be determined in the emergency department all patients who do not have significant premorbid features should proceed to a period of supportive care in the intensive care unit. Therapeutic hypothermia should be considered for these patients.